Enhancer transcription profiling reveals an enhancer RNA-driven ferroptosis and new therapeutic opportunities in prostate cancer - Sheng Ma; Zixian Wang; Zezhong Xiong; Yue Ge; Meng-Yao Xu; Junbiao Zhang; Yuzheng Peng; Qin Zhang; Jiaxue Sun; Zirui Xi; Hao Peng; Wenjie Xu; et al. (Signal Transduction and Targeted Therapy)
Abstract Enhancer RNAs (eRNAs), a subclass of non-coding RNAs transcribed from enhancer regions, have emerged as critical regulators of gene expression; however, their functional roles in prostate cancer remain largely unexplored. In this study, we performed integrated chromatin accessibility and transcriptomic analyses using ATAC-seq and RNA-seq on twenty pairs of prostate cancer and matched benign tissues. By incorporating chromatin immunoprecipitation sequencing data, we identified a subset of differentially expressed eRNAs significantly associated with genes involved in prostate development and oncogenic signaling pathways. Among these, lactotransferrin-eRNA (LTFe) was markedly downregulated in prostate cancer tissues, with functional analyses revealing its tumor-suppressive role. Mechanistically, LTFe promotes the transcription of its target gene, lactotransferrin (LTF), by interacting with heterogeneous nuclear ribonucleoprotein F (HNRNPF) and facilitating enhancer-promoter chromatin interactions. Furthermore, we demonstrate that the LTFe-LTF axis facilitates ferroptosis by modulating iron transport. Notably, androgen receptor (AR) signaling disrupts LTFe-associated chromatin looping, leading to ferroptosis resistance. Therapeutically, co- administration of the AR inhibitor enzalutamide and the ferroptosis inducer RSL3 significantly suppressed tumor growth, offering a promising strategy for castration-resistant prostate cancer. Collectively, this study provides novel insights into the mechanistic role of eRNAs in prostate cancer, highlighting the LTFe-LTF axis as a critical epigenetic regulator and potential therapeutic target for improved treatment outcomes.